TOWARDS GLOBAL HARMONY: PROBLEMS AND PROSPECTS - Raymond, Lorna (Journal of Dharma, 1993)
We are now in the last decade of the twentieth century where the world is in a process of transition. It is a period where all the nations of the world including the Third World Countries are hoping to move forward. At the same time uncertainty, risk and the great complexity around are the challenges that act as constraints to their hopes and aspirations.